Herbal Medicine - Builders, Philip F. (IntechOpen, 2019)
Herbal medicine is a multidisciplinary compilation of topics in herbal medicine that are designed to enlighten all who have a stake in healthcare. In light of the current trends and popularity of herbal medicine, cultural/societal differences and perception, and the relationship with modern healthcare this book presents selected topics to ensure that necessary information on herbal medicine in healthcare is provided. Apart from clarifying certain important complexities and misconceptions on herbal medicine, a general overview of herbal medicine, uses of herbs in the management of diseases, plant secondary metabolites, analytical techniques, applications in stem cell research, use as leads for conventional drug compound development, and research and development of herbal medicines for healthcare are among the major discussions in this book.